Establishing Radiolanthanum Chemistry for Targeted Nuclear Medicine Applications. Issue 6 (9th January 2020) - Aluicio‐Sarduy, Eduardo; Thiele, Nikki A.; Martin, Kirsten E.; Vaughn, Brett A.; Devaraj, Justin; Olson, Aeli P.; Barnhart, Todd E.; Wilson, Justin J.; Boros, Eszter; Engle, Jonathan W.
Abstract: We report the first targeted nuclear medicine application of the lanthanum radionuclides 132/135 La. These isotopes represent a matched pair for diagnosis via the positron emissions of 132 La and therapy mediated by the Auger electron emissions of 135 La. We identify two effective chelators, known as DO3Apic and macropa, for these radionuclides. The 18‐membered macrocycle, macropa, bound 132/135 La with better molar activity than DO3Apic under similar conditions. These chelators were conjugated to the prostate‐specific membrane antigen (PSMA)‐targeting agent DUPA to assess the use of radiolanthanum for in vivo imaging. The 132/135 La‐labeled targeted constructs showed high uptake in tumor xenografts expressing PSMA. This study validates the use of these radioactive lanthanum isotopes for imaging applications and motivates future work to assess the therapeutic effects of the Auger electron emissions of 135 La. Abstract : Lanthanum revealed : The radiochemistry and first targeted in vivo application for the theranostic lanthanum radioisotope pair La‐132/135 is demonstrated.